Owning the Metropolitan Vision: The Case of BLIST - Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 1998)
BLIST, which stands for Baguio, La Trinidad, Itogon, Sablan and Tuba, is a planning area for the Cordillera Administrative Region. It has been identified as a major subregional area due to the fast growth of Baguio City and its spillover to adjacent municipalities. The 1990 earthquake that struck the area has entailed serious planning from authorities, the aim of which is not only the restoration of Baguio City, but also the city's long term reconstruction. This paper reviews the developments and challenges in BLIST, focusing on the necessary steps for addressing the present and future concerns.
Keywords: 330; BLIST infrastructure; metropolitan structure; metropolitan planning and development